Influence of environmental and operational variables in commercial fishery landings: The case of pair trawlers in southeastern Brazil - Rolim, Fernanda Andreoli [UNESP]; Ávila-da-Silva, Antônio Olinto (Elsevier, 2018)
Faced with the overexploitation reality of many of the world fish stocks and climate change, understanding the relationships between catches, fishing strategies and environmental conditions becomes crucial. In this context, this study aimed to describe the correlations between operational and environmental variables in landings of the main fish categories by pair trawl fisheries off the coast of southeastern Brazil. Catch composition varied greatly between 2003 and 2011. This change was mainly related to the shift of the fishing area to greater latitudes and variations in sea surface temperature and chlorophyll concentrations. The physical characteristics of the vessels and fishing gear did not change during the study period. Environmental variables most likely influence stock catchability, primarily by changing their distribution pattern, indicating a shift in ocean characteristics that will influence this dynamic. This draws attention to the need to maintain monitoring programs to apply adequate management measures for the protection of fish populations, consequently ensuring fishing activities in the area.
Keywords: Cluster analysis; Multispecific fisheries; Remote sensing; South Atlantic Ocean; Time lag; Time series